2015
DOI: 10.1016/j.atherosclerosis.2014.10.094
|View full text |Cite
|
Sign up to set email alerts
|

Plasma stromal cell-derived factor 1α/CXCL12 level predicts long-term adverse cardiovascular outcomes in patients with coronary artery disease

Abstract: Objective Stromal derived factor-1α/CXCL12 is a chemoattractant responsible for homing of progenitor cells to ischemic tissues. We aimed to investigate the association of plasma CXCL12 with long-term cardiovascular outcomes in patients with coronary artery disease (CAD). Methods 785 patients aged: 63±12 undergoing coronary angiography were independently enrolled into discovery (N=186) and replication (N=599) cohorts. Baseline levels of plasma CXCL12 were measured using Quantikine CXCL12 ELISA assay (R&D syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 35 publications
1
25
2
Order By: Relevance
“…It is known, however, that SDF‐1 levels are increased in hypertensive states, and that the greater the cardiovascular involvement, the higher SDF‐1 levels . Increased levels of SDF‐1 are also associated with adverse cardiovascular outcomes in individuals with coronary artery disease . Furthermore, increased plasma levels of SDF‐1 are associated with increased mobilization of hematopoietic stem cells, which apparently was not impaired in our study, though other studies have shown a negative effect of propranolol on in vitro cell proliferation …”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…It is known, however, that SDF‐1 levels are increased in hypertensive states, and that the greater the cardiovascular involvement, the higher SDF‐1 levels . Increased levels of SDF‐1 are also associated with adverse cardiovascular outcomes in individuals with coronary artery disease . Furthermore, increased plasma levels of SDF‐1 are associated with increased mobilization of hematopoietic stem cells, which apparently was not impaired in our study, though other studies have shown a negative effect of propranolol on in vitro cell proliferation …”
Section: Discussioncontrasting
confidence: 51%
“…22 Increased levels of SDF-1 are also associated with adverse cardiovascular outcomes in individuals with coronary artery disease. 23 Furthermore, increased plasma levels of SDF-1 are associated with increased mobilization of hematopoietic stem cells, 24 which apparently was not impaired in our study, though other studies have shown a negative effect of propranolol on in vitro cell proliferation. 25 We found no significant differences when we examined specific homing receptors, CXCR-4 and CXCR-7.…”
Section: Discussioncontrasting
confidence: 39%
“…Therefore determination of CXCL12 might be very useful as early additional biomarker ( 11 ). Recently, it was shown that CXCL12 is also associated with heart failure ( 137 ), and that plasma CXCL12 levels are even superior to ­traditional risk factors in predicting adverse cardiovascular outcomes ( 10 ). Although there are still some contradictory clinical results, it is clear that CXCL12 does play a role in atherosclerosis and CVD.…”
Section: Cxcl12mentioning
confidence: 99%
“…In recent years, the chemokine Stromal cell-Derived Factor 1α (SDF1α or CXCL12) has been shown to play a role in cardiovascular diseases [ 1 ] and to be a promising biomarker [ 2 , 3 ]. Together with its receptor, CXCR4, SDF1α is involved in the homing of progenitor/stem cells thereby favoring the repair of injured myocardium through angiogenesis [ 1 , 4 6 ].…”
Section: Introductionmentioning
confidence: 99%